Strategi Peningkatan Pendapatan Daerah Melalui Pajak Bumi Bangunan Di Kabupaten Malang - Perdana, Sukma (Magister Manajemen Universitas Wisnuwardhana, 2023)
This study aims to analyze efforts to increase taxpayers' compliance in paying land and building taxes (PBB). This research is a qualitative research. The informants in this study are employees at the Malang Regency Regional Original Revenue Agency. The data in this study was collected through interview, documentation and observation methods. The results of this study show that taxpayer compliance in the Malang Regency Regional Original Revenue Agency sometimes increases and sometimes decreases. Therefore, there are efforts made by Officers who work at the Malang Regency Regional Original Revenue Agency so that they can increase taxpayers in paying land and building taxes. the existence of optimal management performance in accordance with the field of work and several obstacles related to increasing Land and Building Tax revenues